The discourses of entrepreneurship in brazilian public administration: critical analysis of a contemporary experience - Valadares, Josiel Lopes; Alcântara, Valderí de Castro; Vilas Boas, Ana Alice; Emmendoerfer, Magnus Luiz (Revista de Administração da UFSM, 2018)
This research aims to analyze the elements of social practice within the incorporation discourse of entrepreneurship in the recent experience of the public sector in the State of Minas Gerais. Data were collected on bibliographic and documentary data, using the theoretical and methodological approach of Critical Discourse Analysis (CDA). As a result, the Management Shock appears an ideological element that legitimizes the culture of management in the public sector through the neoliberal hegemonic discourse. By using this strategy, the Public Administration becomes permeated by the market logic that transforms it into a competitive and results searching environment causing typical problems of the capitalist modus operandi. In this regard, the shock spreads the culture of management, naturalizing the values and practices of the business world and discursively legitimizes this model as a necessary and viable option (what is said), while erasing inconsistencies, limitations and ills of the process (silences). In this article these pathways are questioned and the importance of democratization processes lined by citizenship, participation and deliberation is emphasized.